New Si-based multilayers for solar cell applications - Nalini, R Pratibha (Springer, 2011)
In this article, we have fabricated and studied a new multilayer structure Si-SiO(2)/SiN(x )by reactive magnetron sputtering. The comparison between SiO(2 )and SiN(x )host matrices in the optical properties of the multilayers is detailed. Structural analysis was made on the multilayer structures using Fourier transform infrared spectroscopy. The effect of specific annealing treatments on the optical properties is studied and we report a higher visible luminescence with a control over the thermal budget when SiO(2 )is replaced by the SiN(x )matrix. The latter seems to be a potential candidate to replace the most sought SiO(2 )host matrix.